2017
DOI: 10.3389/fcimb.2017.00189
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium canettii Infection of Adipose Tissues

Abstract: Adipose tissues were shown to host Mycobacterium tuberculosis which is persisting inside mature adipocytes. It remains unknown whether this holds true for Mycobacterium canettii, a rare representative of the M. tuberculosis complex responsible for lymphatic and pulmonary tuberculosis. Here, we infected primary murine white and brown pre-adipocytes and murine 3T3-L1 pre-adipocytes and mature adipocytes with M. canettii and M. tuberculosis as a positive control. Both mycobacteria were able to infect 18–22% of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Mtb inside adipocytes also accumulate ILIs (Neyrolles et al, 2006; Agarwal et al, 2014). M. canettii has been shown to replicate and accumulate ILIs inside brown and white preadipocytes (Bouzid et al, 2017). However, a more recent study demonstrated that macrophage lipid body formation during Mtb infection is part of an adaptive immune response activated by IFN-γ (Knight et al, 2018).…”
Section: Biosynthesis Of Tag In Mycobacteriamentioning
confidence: 99%
“…Mtb inside adipocytes also accumulate ILIs (Neyrolles et al, 2006; Agarwal et al, 2014). M. canettii has been shown to replicate and accumulate ILIs inside brown and white preadipocytes (Bouzid et al, 2017). However, a more recent study demonstrated that macrophage lipid body formation during Mtb infection is part of an adaptive immune response activated by IFN-γ (Knight et al, 2018).…”
Section: Biosynthesis Of Tag In Mycobacteriamentioning
confidence: 99%
“…These cells participate in whole-body immune signaling via secretion of adipokines and cytokines such as adiponectin, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, and interleukin (IL)-6 [ 3 ]. Moreover, white adipose tissue (WAT), brown adipose tissue (BAT), and adipocytes are targets of many pathogens such as Trypanosoma cruzi [ 15 ], Staphylococcus aureus [ 25 ], Mycobacterium canettii [ 6 ], and Mycobacterium tuberculosis [ 3 ], resulting in a change of adipose tissue. However, the function of adipose tissue in the progression and pathology of pathogens during infection is remained unclear.…”
mentioning
confidence: 99%
“…The adaptation of M. ulcerans to its new environment was reflected by a larger proportion of bacteria containing ILIs during healing than at the edema stage. The incorporation of host-derived fatty acids into mycobacterial lipid inclusion [ 46–49 ], or directly into mycobacterial membranes [ 50 ] has already been reported. Thus, in times of starvation, M. ulcerans may hydrolyze stored lipids to satisfy its nutrition and energy requirements, as already suggested for M. tuberculosis during latency and reactivation [ 50–53 ].…”
Section: Discussionmentioning
confidence: 99%